Oligoantigenic Diet Improves Children’s ADHD Rating Scale Scores Reliably in Added Video-Rating - Dölp, Anna; Schneider-Momm, Katja; Heiser, Philip; Clement, Christina; Rauh, Reinhold; Clement, Hans-Willi; Schulz, Eberhard; Fleischhaker, Christian (Frontiers in Psychiatry, 2020)
Objectives: The influence of food intake on behavioural disorders was already described in the early 20th century. Elimination of food items (“oligoantigenic diet” (OD)) showed promise to improve attentiondeficit/hyperactivity disorder (ADHD) symptoms. However, only few of the positive results were evaluated by blinded symptom rating. Therefore the present study’s purpose was to evaluate the reliability of a non-blinded rating of the ADHD Rating Scale IV (ARS) for the assessment of OD effects in comparison to with a blinded rating of the ARS based on pseudonymized video recordings. Methods: Ten children (8m/2f) aged 8 to 14 with ADHD according to ICD-10 participated in an uncontrolled, open-label dietary intervention study. Food items, commonly related to intolerances, were eliminated for four weeks. Participants with > 40% improvement in the ARS between T1 (before the diet) and T2 (after the diet) were defined as responders. Nutrients with individual relevance to ADHD symptoms were identified in a following reintroduction phase (T3-T4) lasting 8 -16 weeks. The ARS was completed by a non-blinded child and adolescent psychiatrist (T0-T4). Sessions were recorded on video, pseudonymized, and evaluated by three blinded raters. Complete data were captured for eight children. The inter-rater reliability between the non-blinded therapist and every blinded rater was determined with intra-class correlation coefficient (ICC). The Spearman correlation (rho) between the non-blinded and blinded rating was calculated for each rater. Results: Two blinded raters and the non-blinded rater considered 5 of 8 (62.5%) children as responders, whereas one blinded rater deviatedfrom the others in one case thus considering only 4 of 8 children as responders to the diet. Inter-rater reliability was assessed by evaluating 33 videos: The intra-class coefficients were >.9 for all raters and the Spearman rho between the raters were high (n=33; rater 1: rho >0.9, p<.0001), respectively. Discussion: As both, blinded and unblinded ratings of the ARS, revealed significant improvements of ADHD symptoms in children following an OD in this uncontrolled trial, RCTs are urgently needed to get unbiased effect sizes in combination with more objective measuring methods.